Dampak Kompensasi, Beban Kerja dan Pengembangan Sumber Daya Manusia Terhadap Kepuasan Kerja pada PT. Perkebunan Nusantara IV (Persero) Medan - Ridofals Caniago; Bagus Handoko; Sopi Pentana (Journal of Management and Creative Business, 2024)
The purpose of this study was to examine and analyze the effect of compensation, workload and human resource development on job satisfaction at PT Perkebunan Nusantara IV (Persero) Medan partially or simultaneously. The approach used in this study is a causal approach. The population in this study were all employees at PT. Perkebunan Nusantara IV (Persero) Medan as many as 389 employees. Based on the slovin calculation, the number of samples in this study were 80 employees of PT. Perkebunan Nusantara IV (Persero) Medan. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study uses a quantitative approach using statistical analysis using multiple linear regression, classical assumption test, hypothesis testing and coefficient of determination test. The results of this study prove that compensation, workload and human resource development partially or simultaneously affect job satisfaction at PT Perkebunan Nusantara IV (Persero) Medan